Reducing fear and avoidance of memory loss improves mood and social engagement in community-based older adults: a randomized trial - Francesca R Farina; John Regan; Melissa Marquez; Hosanna An; Patricia O’Loughlin; Pavithra Pavithra; Michelle Taddeo; Rachel C Knight; Marc Bennett; Bert Lenaert; James W Griffith (BMC Geriatrics, 2023)
Abstract Background Alzheimer’s disease and related dementias (ADRD) are among the most feared age-related conditions. The aim of this study was to evaluate a brief psychological intervention to promote adaptive coping in older adults experiencing heightened fear of ADRD and investigate positive downstream effects on health-related secondary outcomes, including frequency of reported memory failures, psychosocial functioning, and quality of life. Methods Eighty-one older adults were recruited and randomized into REFRAME or active control intervention arms. Both groups received psycho-education and training in mindful monitoring of fears related to ADRD. The REFRAME group received an additional behavioral activation component intended to disrupt maladaptive avoidant coping (i.e., avoidance) strategies. Both groups completed 3-weeks of intervention exercises with accompanying questionnaires (baseline, mid- and post-intervention and 4-week follow-up). Results Adherence was strong (> 75%). We observed a significant reduction in ADRD-related fear and avoidance in both groups. Significant reductions were also observed for frequency of self-reported memory failures, anxiety, and depression. Depression was significantly reduced in the REFRAME group compared to the control group. Significant increases in participants’ ability to participate in social activities and well-being were also observed. Conclusions Findings suggest that a brief psychological intervention can mitigate ADRD-related fears and avoidant coping in older adults, and that benefits extend to broader health-related outcomes including anxiety, depression, social functioning, and well-being. Addressing ADRD-related fear has implications for healthy aging and risk reduction, as individuals may be more likely to engage in activities that are protective against ADRD but were previously avoided. Trial registration : https://clinicaltrials.gov/ct2/show/NCT04821960 .